Perbandingan Adverbia Penanda Waktu Bahasa Korea dan Bahasa Indonesia - Jayanti Megasari; Ashanti Widyana (Universitas Gadjah Mada, 2020)
This is a comparative study of Korean and Indonesian language. This study aims to describe the form of time markers adverbs in Korean and Indonesian and also to analyze the differences and similarities of the time markers of Korean and Indonesian language. The simple sentences in Korean are translated into Indonesian by following the Indonesian language rules that apply as objects of analysis. It is found that (1) the adverb form of time marker in Korean and Indonesian has very noticeable differences; (2) the time marker in Korean is adverb but it is not applied in Indonesian language. On the other hand, the time marker in Indonesian is adverb but in Korean, it is only suffix particles.